Against Representation: A Note on Jorge Luis Borges’ Aleph - Ilan Stavans (Studies in 20th & 21st Century Literature, 2017)
Faced with the need to represent Jorge Luis Borges’s classic tale “The Aleph,” which also gives name to his 1949 collection of stories, for decades publishers have resorted to a variety of dependable images, including works by Borges’s friend Xul Solar. Yet the argument of the tale is that no human language, either verbal or visual, is capable of summing up the fullness of the object Borges’s narrator discovers in a dark Buenos Aires basement. That object—the universe itself—is unrepresentable.
Keywords: Borges; Aleph